2018
DOI: 10.1007/s00221-018-5224-4
|View full text |Cite
|
Sign up to set email alerts
|

The ipsilateral corticospinal responses to cross-education are dependent upon the motor-training intervention

Abstract: This study aimed to identify the ipsilateral corticospinal responses of the contralateral limb following different types of unilateral motor-training. Three groups performing unilateral slow-paced strength training (SPST), non-paced strength training (NPST) or visuomotor skill training (VT) were compared to a control group. It was hypothesised that 4 weeks of unilateral SPST and VT, but not NPST, would increase ipsilateral corticospinal excitability (CSE) and reduce short-interval cortical inhibition (SICI), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 79 publications
2
18
0
Order By: Relevance
“…Based on adult research, increases in corticospinal excitability (Kidgell et al 2011;Leung et al 2018) and decreased corticospinal inhibition (i.e. short interval cortical inhibition) of the contralateral limbs (Latella et al 2012;Leung et al 2018) could contribute to enhanced motor unit recruitment and rate coding-induced increases in strength and power (Behm 1995;Behm et al 2008) with the training effects observed with children in this study. However, a meta-analysis by Manca et al (2018) indicated that the magnitude of corticospinal excitability did not correlate with cross-education changes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Based on adult research, increases in corticospinal excitability (Kidgell et al 2011;Leung et al 2018) and decreased corticospinal inhibition (i.e. short interval cortical inhibition) of the contralateral limbs (Latella et al 2012;Leung et al 2018) could contribute to enhanced motor unit recruitment and rate coding-induced increases in strength and power (Behm 1995;Behm et al 2008) with the training effects observed with children in this study. However, a meta-analysis by Manca et al (2018) indicated that the magnitude of corticospinal excitability did not correlate with cross-education changes.…”
Section: Discussionmentioning
confidence: 72%
“…Farthing in his review (Farthing 2009) explains that a mechanism of cross-education would be related to plasticity of the cortical pathways involved in motor planning input as well as plasticity in the motor command of the motor cortex increasing agonist activation (Hortobagyi et al 1997;Farthing et al 2007) and decreasing co-contractions (Carolan and Cafarelli 1992). Based on adult research, increases in corticospinal excitability (Kidgell et al 2011;Leung et al 2018) and decreased corticospinal inhibition (i.e. short interval cortical inhibition) of the contralateral limbs (Latella et al 2012;Leung et al 2018) could contribute to enhanced motor unit recruitment and rate coding-induced increases in strength and power (Behm 1995;Behm et al 2008) with the training effects observed with children in this study.…”
Section: Discussionmentioning
confidence: 99%
“…strength training, or motor learning and skill acquisition. Evidence has suggested that the level of contractions and types of motor training can influence the amount of crossed facilitation observed in the untrained muscle 21,55 . To the best of our knowledge, this is the first study reporting that unilateral arm cycling alone for 20 min or less is unlikely to induce acute changes in corticospinal drive to the trunk muscle.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several studies have reported no change in the ipsilateral TMS responses, 12,13,14 whilst others have reported increased ipsilateral M1 excitability and reduced intracortical inhibition. 8,15,16 Irrespective of the above, it has been suggested that changes in excitability of the ipsilateral M1 could be due to neural mechanisms associated with cross-activation. 17,18,19 Cross-activation is based upon the observation that unilateral muscle actions result in a bilateral increase in corticospinal excitability 9,17,20,21,22 and a decrease in intracortical inhibition of the ipsilateral M1.…”
Section: Introductionmentioning
confidence: 99%